TRANSPARANSI PELAYANAN JAMINAN SOSIAL NASIONAL (JSN) KETENEGAKERJAAN DI KABUPATEN GOWA - Hidayatullah Hidayatullah; Andi Nuraeni Aksa; Ihyani Malik (Department of Government Studies Universitas Muhammadiyah Makassar, 2014)
This study aims to determine the transparency of the Social Security services Employment in Gowa. Penelitiian type used in this approach with a qualitative description by conducting interviews. Data collection techniques in this research is observation, interview, and documentation. The results showed that: the provision of information with clarity indicator procedures, clarity of costs already quite transparent; easy access to information with indicators of the ease of getting information directly or indirectly, is also quite easy to obtain; Develop a complaints mechanism if there are rules that have been violated or request to pay a bribe to the service indicator complaints have been made; Improving the flow of information through cooperation with mass media and non-governmental institutions have been established. Efforts are being made to bring transparency BPJS Employment services Employment WSN WSN is to provide information regarding employment through labor website, then one-stop services, namely services performed in one room and provide one-day service care provision. Penelitian ini bertujuan untuk mengetahui transparansi pelayanan JSN Ketenagakerjaan di Kabupaten Gowa. Jenis yang digunakan dalam penelitiian ini adalah pendekatan deskripsi kualitatif dengan dengan melakukan wawancara. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa: penyediaan informasi dengan indikator kejelasan prosedur-prosedur, kejelasan biaya-biaya sudah cukup transparan; kemudahan akses informasi dengan indikator kemudahan mendapatkan informasi langsung maupun tidak langsung juga cukup mudah didapatkan; Menyusun suatu mekanisme pengaduan jika ada peraturan yang dilanggar atau permintaan untuk membayar uang suap dengan indikator layanan pengaduan telah dilakukan; Meningkatkan arus informasi melalui kerjasama dengan media massa dan lembaga non pemerintah telah terjalin. Upaya yang dilakukan BPJS Ketenagakerjaan dalam mewujudkan transparansi pelayanan JSN Ketenagakerjaan adalah memberikan informasi terkait JSN Ketenagakerjaan melalui website tenagakerja, kemudian pelayanan satu atap yaitu pelayanan yang dilakukan dalam satu ruangan dan menyediakan penyediaan pelayanan one day service.